2000
DOI: 10.1007/s001250051569
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that single nucleotide polymorphism in the uncoupling protein 3 (UCP3) gene influences fat distribution in women of European and Asian origin

Abstract: The rising prevalence of Type II (non-insulin-dependent) diabetes and obesity worldwide poses a serious challenge to human health and incomplete understanding of the aetiological basis of these closely related metabolic conditions is a major impediment to improved management. There is considerable evidence to suggest that primary abnormalities in energy balance contribute to the pathogenesis of diabetes and obesity [1]. Reduced energy expenditure is correlated with subsequent weight gain [2] and normoglycaemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 34 publications
2
48
0
1
Order By: Relevance
“…12,13 The following will be investigated in this study: (1) two UCP2 gene polymorphisms, including the G-866A polymorphism in the promoter region, 14 A55V (Ala55Val) polymorphism in exon 4; 15,16 and (2) two UCP3 gene polymorphisms, including the C-55T polymorphism of the promoter [17][18][19] and V102I (Val102Ile) in exon 3. 9 These variants have been reported to be associated with body mass index (BMI), 3,[18][19][20] sleeping metabolic rate, energy expenditure, 12 waist-to-hip ratio 17 and diabetes. 21 But results of several studies have shown no significant association with non-insulin-dependent diabetes mellitus, 17,22,23 RMR 24 and BMI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 The following will be investigated in this study: (1) two UCP2 gene polymorphisms, including the G-866A polymorphism in the promoter region, 14 A55V (Ala55Val) polymorphism in exon 4; 15,16 and (2) two UCP3 gene polymorphisms, including the C-55T polymorphism of the promoter [17][18][19] and V102I (Val102Ile) in exon 3. 9 These variants have been reported to be associated with body mass index (BMI), 3,[18][19][20] sleeping metabolic rate, energy expenditure, 12 waist-to-hip ratio 17 and diabetes. 21 But results of several studies have shown no significant association with non-insulin-dependent diabetes mellitus, 17,22,23 RMR 24 and BMI.…”
Section: Introductionmentioning
confidence: 99%
“…9 These variants have been reported to be associated with body mass index (BMI), 3,[18][19][20] sleeping metabolic rate, energy expenditure, 12 waist-to-hip ratio 17 and diabetes. 21 But results of several studies have shown no significant association with non-insulin-dependent diabetes mellitus, 17,22,23 RMR 24 and BMI. 9,[25][26][27] These relationships between polymorphisms in UCP2/UCP3 genes, BMI and obesity-related phenotypes are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Despite strong functional evidence for the UCP2 Ϫ866 G/A and UCP3 Ϫ55 C/T polymorphisms, previous association studies of both UCP2 and UCP3 gene variants have not been consistent. Several studies found that these functional variants exhibited significantly increased (8,9,13) or decreased (14 -16) type 2 diabetes risk, but others did not report any significant associations (10,17). Such discrepancies may be attributable to differences in study design (population based vs. hospital based), selection and ascertainment schemes, sample sizes, or statistical analysis strategies.…”
mentioning
confidence: 99%
“…The T allele in UCP3 C ! T ( À 55) polymorphism was associated with increased waist to hip ratio in women (Cassell et al, 2000), and the T/T genotype with higher BMI . The À 55 T/T genotype was also found to be associated with an atherogenic lipid profile in French Caucasians, and the T/T genotype conferred decreased risk of Type 2 diabetes in French but not in Danish subjects Data are number of subjects (percent).…”
Section: Discussionmentioning
confidence: 95%